OFR-63-80 State-Of-The-Art Of Sampling And Analysis For Diesel Exhaust Contaminants - K. T. Menzies (The National Institute for Occupational Safety and Health (NIOSH), 1979)
Over 1500 literature citations related to diesel exhaust sampling and analysis were obtained as a result of both computer and manual searches of nine data bases. Abstracts and hard copies of relevant citations were reviewed and those considered appropriate for evaluation were included in a bibliography. Based on the literature collected, available sampling and analysis methods for the following diesel exhaust contaminants were evaluated: CO, CO2, NO, NO2, Hydrocarbons, Particulates, PNA, S04, Oxygenates Emphasis was given to both laboratory and field methods for these species. Methods were evaluated on the basis of sensitivity, selectivity, accuracy and reliability and a selected list of preferred methods was developed for each compound/ class. The selected methods were additionally evaluated through communication with current investigators. Sampling and analysis methods for all compounds except CO and CO2 were observed to have some unreliability. Recommendations were made for future research to develop, improve, and validate methods.